2022
DOI: 10.1101/2022.01.28.477987
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Mapping SARS-CoV-2 antigenic relationships and serological responses

Abstract: During the SARS-CoV-2 pandemic, multiple variants with differing amounts of escape from pre-existing immunity have emerged, causing concerns about continued protection. Here, we use antigenic cartography to quantify and visualize the antigenic relationships among 16 SARS-CoV-2 variants titrated against serum samples taken post-vaccination and post-infection with seven different variants. We find major antigenic differences caused by substitutions at positions 417, 452, 484, and possibly 501. B.1.1.529 (Omicron… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

29
116
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 64 publications
(157 citation statements)
references
References 86 publications
29
116
2
Order By: Relevance
“…lineage specific responses, with some cross reactivity. Antigenic cartography analyses indicated that all VOCs except Omicron belong to one large antigenic cluster, whereas Omicron forms a new cluster, escaping vaccine or convalescent sera 7,8 .…”
Section: Limited Antibody Cross-reactivitymentioning
confidence: 99%
See 1 more Smart Citation
“…lineage specific responses, with some cross reactivity. Antigenic cartography analyses indicated that all VOCs except Omicron belong to one large antigenic cluster, whereas Omicron forms a new cluster, escaping vaccine or convalescent sera 7,8 .…”
Section: Limited Antibody Cross-reactivitymentioning
confidence: 99%
“…Boundaries of each serotype may be difficult to estab lish, owing to the generally high rate of change, com bined with recurrent or convergent changes in various lineages. Within each serotype, different antigenic clus ters may be present, indicating a continuum of immune escape and immunodominance patterns 8 , and bounda ries will likely evolve when new variants appear. In par allel, repeated exposure to the virus or vaccinal antigens will increase the breadth and potency of the humoral response, limiting serotype specificity.…”
Section: Limited Antibody Cross-reactivitymentioning
confidence: 99%
“…The same clustering based on E484K and L452R/Q was observed in the pseudovirus maps. A recently study by Wilks and colleagues used human sera to generate an antigenic map 31 . Both the maps from our study and the map from Wilks and colleagues show the same clustering of variants containing mutations at position 484, 417 and 452, indicating that hamsters and humans generate similar antibody responses.…”
Section: Neutralizing Activity Of Human Sera Against Omicron Ba1 and Ba2mentioning
confidence: 99%
“…Omicron demonstrated clearly that SARS-CoV-2 is capable of considerable antigenic escape over a relatively short period of time. The variant features at least 50 amino acid mutations compared with the ancestral Wuhan-Hu-1 reference strain 4 and is highly antigenically divergent from earlier VOCs 5 . Its explosive spread in highly immune populations revealed that these mutations enable the variant to easily infect individuals with immunity due to previous infection or vaccination.…”
mentioning
confidence: 97%